Robot Control Strategies for Task Allocation with Connectivity Constraints in Wireless Sensor and Robot Networks - Wichmann, Andrew; Korkmaz, Turgay; Tosun, Ali S. (IEEE transactions on mobile computing, 2018)
Mobility within Wireless Sensor Networks (WSNs) has been widely considered for data collection tasks, where mobile robots physically collect the data from the sensors and return to the base station. Although this approach has proven to be useful in prolonging the lifetime of these networks, it cannot meet the requirements of real-time data collection tasks. For such tasks, we need to utilize mobile robots to create a connected path from the base station to the event, as well as use in-network forwarding through that path. This will provide a longer lifetime while addressing efficiency and scalability issues because mobile robots have a larger and renewable energy reserve, a longer transmission range, and capacity. One of the fundamental problems is how to coordinate robots to establish a connected path from the event location to the base station. We consider this fundamental problem with two objectives, namely minimizing distance traveled by the robots and minimizing hop count (the number of robots used on paths) under the constraints of satisfying the path and/or network connectivity. After mathematically formulating the underlying problems and discussing their NP-hardness, we propose various heuristic solutions. We then demonstrate the efficacy of our proposed solutions through extensive simulations.